A practical synthesis of voxelotor. (22nd July 2022) - Kang, Linlin; Mao, Yongjun; Jiang, Shun; Lu, Sheng
Abstract: An improved and practical synthesis of voxelotor (1) was developed, from the commercially available chemicals pyrazole, 2‐chloronicotinic acid, and dimethoxybenzene. The key intermediate (2‐[1‐isopropyl‐1 H ‐pyrazol‐5‐yl]pyridin‐3‐yl)methanol (8) was prepared in 45% yield over 4 steps, including reduction and cross‐coupling condensation. 2, 6‐Dihydroxybenzaldehyde (24 ) was prepared in 68% yield over 2 steps. Finally, 1 was obtained from this convergent synthetic route through 8 steps in total 25% yield and 99.2% purity on a 20 grams scale. Abstract : Practical Synthesis of Voxelotor.